2009
DOI: 10.1016/j.ijheatfluidflow.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inflow conditions on the transition to turbulence in large eddy simulations of spatially developing mixing layers

Abstract: Large Eddy Simulations (LES) of spatially developing turbulent mixing layers have been performed for flows of uniform density and Reynolds numbers of up to 50,000 based on the visual thickness of the layer and the velocity difference across it. On a fine LES grid, a validation simulation performed with a hyperbolic tangent inflow profile produces flow statistics that compare extremely well with reference Direct Numerical Simulation (DNS) data. An inflow profile derived from laminar Blasius profiles produces a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…The one of greatest concern in the present context is its prediction of a non-zero eddy viscosity in regions of laminar flow. As has been shown in previous work (McMullan et al 2009), this can have the effect of damping the instability modes in the pre-transition part of the mixing layer and delaying the transition itself.…”
Section: Sgs Modellingsupporting
confidence: 54%
See 2 more Smart Citations
“…The one of greatest concern in the present context is its prediction of a non-zero eddy viscosity in regions of laminar flow. As has been shown in previous work (McMullan et al 2009), this can have the effect of damping the instability modes in the pre-transition part of the mixing layer and delaying the transition itself.…”
Section: Sgs Modellingsupporting
confidence: 54%
“…In earlier work by the present authors (McMullan 2005;McMullan et al 2009) comparisons have also been made with the results of a DNS and of a simulation performed with a 'structure-function' SGS model (Metais & Lesieur 1992). These comparisons showed no evidence of any significant backscatter from the unresolved to the resolved scales (Piomelli et al 1991) in these threedimensional spatially evolving mixing layers with the inflow fluctuation levels of interest here.…”
Section: Sgs Modellingmentioning
confidence: 63%
See 1 more Smart Citation
“…Initially-laminar spatial mixing layer simulation inflow conditions are typically produced from a base mean velocity profile onto which pseudo-random white noise fluctuations are superimposed at each time step. 21,23,24,25 In the pre-transition region the nature of the imposed disturbances influences the nature of the laminar vortices. Three-dimensional random disturbances result in structures which undergo localised pairings, whilst highly two-dimensional random disturbances produce concentrated streamwise vortices between the primary rollers.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this sensitivity has been demonstrated to depend on whether or not the fluid flowing into the mixing layer's splitter-plate geometry was itself initially either laminar or turbulent. In addition, McMullan et al [13] recently showed that initial conditions may even affect direct numerical simulations, the benchmark for turbulence calculations. What we present here shows that in our shock-driven HED mixing layer, which has a more than adequately developed dynamic Reynolds number (Re d ¼ 10 7 ) to have evolved to be a fully turbulent mixing layer, the initial scale lengths set by the shocksurface interactions play the role of inflow condition scale lengths and influence the intermediate late time mixing of the developed flows.…”
mentioning
confidence: 99%